Pengaruh Social Media Marketing, Product Quality, Price, Brand Image, dan E-WOM Melalui Trust terhadap Willingness to Pay Makanan Impor Premium - Kesumahati, Erilia; Marco, Alysia Callista; Yuwono, Wisnu (Universitas Batanghari Jambi, 2026)
This study aims to explore how social media marketing, product quality, price, brand image, and electronic word of mouth influence willingness to pay by involving 381 respondents in Batam City, analyzed using the PLS-SEM approach. The results of this study indicate that there is a positive and significant influence between the variables of social media marketing, product quality, price, brand image, and electronic word of mouth on willingness to pay for premium imported food products in Batam City.